The Effect of Foundation Flexibility on Probabilistic Seismic Performance of Plan-Asymmetric Buildings with Different Strength Distributions - Sahar Mohammadzadeh Osalu; Hamzeh Shakib (Advances in Civil Engineering)
In this research, the probabilistic seismic performance of asymmetric reinforced concrete wall-frame buildings with different strength distributions incorporating foundation flexibility effects is examined. By using probability-based performance evaluation approach, it is possible to provide a more accurate prediction of the different strength distribution effect on the seismic performance of asymmetric buildings and find the most efficient strength distribution for meeting each performance level. These efficient distributions can be adopted in the performance-based design of asymmetric buildings. For this purpose, first, the regression analysis and the concepts of efficiency and sufficiency were used to determine an optimal intensity measure (IM) for incremental dynamic analysis and evaluating the seismic response of the considered building models. Then, the proper magnitude of interstory drift capacity for this type of buildings in each limit state was estimated using the damage index concept. Finally, the effects of different strength distributions and the flexibility of foundation were studied on the seismic performance of the asymmetric buildings by investigating the mean annual frequencies of exceeding structural performance levels and confidence levels to satisfy performance objectives. It is concluded that irregular distributions of stiffness and strength in the plan of a building highly affect the seismic performance of buildings. Also, the results show that the optimum strength distribution is a function of the objective performance level and these optimum strength distributions are the same for both fixed- and flexible-base conditions. Meanwhile, the flexible effect of foundation increases the mean annual frequencies of exceedance within the range of 10% to 45% and significantly decreases the confidence levels in most cases.